Model Blended Learning Dengan Menerapkan Experiential Learning - Diana Ariani (Jurnal Pembelajaran Inovatif, 2018)
This article describes the Blended Learning training model specifically developed by Experience Learning. The model in question is the APKL model, and the model is designed to develop compound learning through the use of experimental learning. APKL itself stands for "analysis, selection, development and implementation." Because this model focuses on blended learning, not an online learning model, Blended Learning will provide a personal learning experience with a variety of learning modes and application-based technology environments.